Lactate dehydrogenase, Beta-2 Microglobulin Levels and CD4/CD8 Lymphocyte Ratio in Patients with Mycosis Fungoides in Stage 1A - Gülseren, Duygu; Bostan, Ecem; Doğan, Sibel; Yalıcı-Armağan, Başak; Akdoğan, Neslihan; Ersoy-Evans, Sibel; Elçin, Gonca; Karaduman, Ayşen; Atakan, Nilgün (Acta Medica, 2020)
Objective: Mycosis fungoides is the most common type of primary cutaneous T-cell lymphomas. In this study, we aimed to investigate the biochemical parameters of beta-2 microglobulin, lactate dehydrogenase, CD4/CD8 lymphocyte ratio determined by flow cytometry, and T cell clonality in patients with MF and to correlate these parameters in stage 1A and other stages. Materials and Methods: A hundred sixty-one (87 Male, 74 Female) patients followed-up between January 1995 and January 2019 were retrospectively evaluated. Patients’ demographics, stage of the disease, peripheral lymph node and organ involvement, peripheral blood beta-2-microglobulin, lactate dehydrogenase levels, CD4/CD8 + lymphocyte ratio and presence of T cell clonality in biopsy samples were evaluated. Results: Median beta-2 microglobulin levels were 1608.5 ng/ml for stage 1A and 1970.5 ng/ml for other stages. Peripheral blood median CD4/CD8 lymphocte ratio was 1.60 for stage 1A and 1.85 for other stages. We found statistically significant difference between two groups in terms of beta-2 microglobulin levels and peripheral blood median CD4/CD8 lymphocte ratio (p=0.001, p=0.04). No statistically significant difference was found between two groups in terms of lactate dehydrogenase levels and T-cell clonality (p=0.234, p=0.525). Conclusion: Our study supports that high peripheral blood beta-2 microglobulin level and CD4/CD8 lymphocyte ratio at the time of diagnosis may imply advanced stage and poor prognosis in Mycosis Fungoides.